Israiliyyat Dalam Tafsir Al-Quran - Yumni, Firda Aufa; Alwizar, Alwizar; Yusuf, Kadar M (CV. Rayyan Dwi Bharata, 2025)
Israiliyyat in Qur'anic exegesis refers to narratives and information derived from Jewish and Christian traditions that have entered into the interpretation of Qur'anic verses through the reports of early Muslim scholars, including companions and successors (tabi'in). This article critically examines the definition, classification, and position of Israiliyyat within the tradition of tafsir, as well as the methodologies adopted by scholars in dealing with such reports. Israiliyyat is categorized based on the authenticity of its transmission (sound or weak) and its compatibility with Islamic teachings (accepted, rejected, or suspended). While classical exegetes often used Israiliyyat to elaborate on historical accounts in the Qur'an, modern scholars tend to approach them with skepticism or outright rejection to preserve the purity of Islamic doctrine. The use of Israiliyyat presents a double-edged impact: it may enrich historical context but can also mislead the understanding of Islamic teachings if not critically verified. Therefore, caution in employing Israiliyyat is essential in Qur'anic interpretation to protect the integrity of Islamic beliefs and the accurate understanding of divine revelation.